The development of wayfinding abilities in children: Learning routes with and without landmarks. (March 2015) - Lingwood, Jamie; Blades, Mark; Farran, Emily K.; Courbois, Yannick; Matthews, Danielle
Abstract: Young children experience wayfinding difficulties. A better understanding of the development of wayfinding abilities may inform strategies that can be used to improve these skills in children. The ability to learn and remember a route was assessed in 220 6-, 8-, and 10-year old children and adults. Participants were shown a route in a virtual environment, before they were asked to retrace this route until they had achieved two consecutive trials without error. The virtual environment contained (i) no landmarks (ii) landmarks or (iii) landmarks that were verbally labelled. Adults, 10-year-olds and most 8-year-olds learnt the route when landmarks were present, but not all the 6-year-olds were successful. All age groups of children improved when the landmarks were labelled. Children were much poorer when there were no landmarks. This is the first study to distinguish between route learning dependent on landmarks, and route learning without landmarks (i.e. dependent on directions). Highlights: The ability to learn a route in a virtual environment was assessed. The virtual environment contained either (i) no landmarks (ii) landmarks or (iii) landmarks that were verbally labelled. 6-, 8- and 10-year olds were much poorer when there were no landmarks. Adults, 10-year-olds and most 8-year-olds learnt the route when landmarks were present, but not all the 6-year-olds did. All age groups of children improved when the landmarks were labelled for them.